Calculation of tourist reception with multicriteria methodology at Huagapo grotto: Analysis in pandemic - Huaroc-Ponce, Edwin J. (2021)
The Huagapo grotto located in Palcamayo, Tarma, Junín region - Peru, at 3572 m.a.s.l. It was traveled up to 2800 meters deep, for tourist use it is traveled 212 meters (dry route). The work is based on the tourist carrying capacity calculated with the Cifuentes methodology and improved with the CATUM multicriteria tourist reception calculation, finding the physical carrying capacity CCF, the correction factors Fc, real carrying capacity CCR, management capacity CM and effective carrying capacity CCE or called tourist carrying capacity CCT, CATUM methodology for weighting correction factors with multicriteria analysis and the 3S methodology at three levels. The results were: CCF= 2692 visits; Fc= 0.324002; CCR=1323, CCE-Cifuentes= 483 visitors, CATUM=732 visitors per day, with a difference of 249 visitors between both methodologies. It is concluded that the CATUM methodology serves to perform an integral analysis using a multi-criteria adjustment that helps to consider the number of visitors in an efficient way.